Аналіз основних ризиків при впровадженні GDPR - Товкун, Ю. І. (ХНУРЕ, 2022)
The modern vision of personal data protection involves an ongoing assessment of the risks that may arise for both the campaign and for other entities that are in one way or another associated with the company in the processing of personal data.